USING THE INDONESIAN MANCHESTER CLINICAL PLACEMENT INDEX (I-MCPI) TO ASSESS THE QUALITY OF HOSPITAL-BASED AND COMMUNITY-BASED CLINICAL LEARNING ENVIRONMENT - Audelia Kathleen Sulaiman; Carolyn Carolyn; Natalia Puspadewi; Elisabeth Rukmini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Clinical placement is crucial to develop the fundamental competencies in providing patient care. Therefore, clinical learning environment (CLE) assessment is necessary to ensure its quality. The Indonesian Manchester Clinical Placement Index (I-MCPI) is an instrument for assessing the quality of the learning environment and the quality of training in both hospital and community placements. This study aimed to (1) measure the CLE quality of a school of medicine in Jakarta using I-MCPI and (2) explore the qualitative data resulted from the I-MCPI to draw a comprehensive conclusion about CLE.Methods: 155 respondents filled the online I-MCPI, and ten respondents participated in the in-depth interviews. The quantitative data were analyzed using the guideline provided by the original MCPI. The qualitative data analysis was performed using content analysis method.Results: Quantitative data resulted in ranks of the 18 clinical placements, including primary teaching hospital and its network clinical placements. Trends in Primary Health Care (PHC) placement showed lower rank on the CLE and the training quality. The primary teaching hospital was in the sixth position. The qualitative results identified issues of the supervisor’s role, students’ involvement, and learning facilities were identified as significant factors that influenced CLE.Conclusion: Most respondents were satisfied with the quality of learning in clinical rotation at the school. However, respondents suggested more support for students to be actively involved in clinical services, perform clinical skills, and encourage learning facilities to optimize the CLE.